PL03 Does domiciliary welfare rights advice improve health related quality of life in independent-living, socio-economically disadvantaged people aged ≥60 years, recruited via primary care? Randomised controlled trial with embedded economic, qualitative and process evaluations. (13th September 2016) - White, M; Howel, D; Moffatt, S; Vale, L; Haighton, C; McColl, E; Bryant, A; Becker, F; Steer, M; Lawson, S; Aspray, T; Milne, E
Abstract : Background: Strong socio-economic gradients in health suggest that access to additional financial and material resources could lead to improved health. Welfare rights advice can substantially increase disposable income among older people eligible for unclaimed benefits. Whether the receipt of such interventions improves health has not been rigorously evaluated. Methods: Randomised wait-list controlled trial with individual allocation, stratified by general practice. Participants were aged ≥60 years, recruited from general practices in socio-economically deprived areas of north east England. Intervention comprised welfare rights advice consultations and active assistance with benefit claims offered and delivered in participants' homes, tailored to individual needs, by a trained welfare rights advisor. Control participants received usual care. Outcomes were assessed in interviews prior to randomisation, and after 24 months. Primary outcome was CASP-19 score (range 0–57). Secondary outcomes included changes in income, social and physical function, and cost-effectiveness. Intention to treat analysis compared outcomes in intervention and control arms using multiple linear regression, with adjustment for baseline values, general practice and key effect modifiers. Further exploratory analyses were undertaken. Qualitative interviews with purposive samples from both trial arms were thematically analysed. Results: Of 3912 primary care patients approached, 755 consented and were randomised [381 Intervention, 374 Control]. Follow-up data were available on 562 (74.4%) at 24 m. Trial arms were balanced at baseline with respect to social and demographic characteristics and trial outcomes. Among the intervention group, 335 (88%) received the intervention as intended and 84 (22%) were awarded additional material or financial (mostly non-means tested, health-related) benefits. Mean CASP-19 scores were 42.9 (Intervention) and 42.4 (Control) at 24 m [adjusted mean difference 0.3 (95% CIs −0.8, 1.5)]. There were no significant differences in secondary outcomes, except Intervention participants reported receiving more home care at 24 m (53.7 (Intervention) vs 42.0 (Control) hrs/wk [adjusted mean difference 26.3 (95% CIs 0.8, 56.1)]. Exploratory quantitative analyses did not provide evidence to support an intervention effect and economic evaluation suggested the intervention was unlikely to be cost-effective. However, qualitative data from 50 interviews (31 women, 19 men) suggested important improvements in quality of life among those who received additional benefits. Discussion: The trial found no effects of the intervention. However, fewer participants than anticipated received additional welfare benefits, and participants were healthier and more affluent than expected. Our findings do not support the delivery of domiciliary welfare rights advice to promote health in this population. Better intervention targeting may reveal worthwhile health impacts.